Agents on the move [mobile software agents]. - Morreale, P.
The author describes a new kind of software, based on artificial intelligence research, that can move itself from place to place to help people work more effectively. Known as agents, these artificial assistants are software components that live inside computer environments. Developed out of research in artificial intelligence (AI), agents were made in a variety of forms to perform all sorts of useful work-including obtaining airline departure dates and times, filtering e-mail for messages the user considers important, alerting users to significant stock price changes, and a host of other tasks. At first, agents were constrained to a single computer or at most to a single computing environment-a closed, homogenous network of, say, Unix platforms. Their behavior was limited and all the tasks they could do had to be pre-established. Today, agents are breaking the bonds that confine them to a single environment while learning new ways of accomplishing tasks on their own, based on their experience. The newcomers are called mobile agents, because they can move from one computer to another. As they emerge from the shadow of AI research, they are bringing together telecommunications, software, and distributed-system technologies to create new ways of getting things done
Keywords: Artificial assistants; Artificial intelligence research; Distributed-system technologies; Mobile agents; Object oriented code; Software; Software agents; Software components; Telecommunications